2001
DOI: 10.3748/wjg.7.657
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ABO blood groups and carcinoma of esophagus and cardia in Chaoshan inhabitants of China

Abstract: ABO blood group B is associated with the incidence of CC in male individuals and carcinoma in the upper third esophagus. The distribution of ABO blood groups varies in the different geographical and ethnic groups. As a result, proper controls are very important for such studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Numerous studies show that the percentage of ABO and Rh blood types was found to be quite different in different samples of patients [18][19][20][21][22][23][24][25]. According to those findings, we assume that certain connection between predisposition to CDH and frequencies of ABO and Rh blood types exists.…”
Section: Introductionmentioning
confidence: 54%
“…Numerous studies show that the percentage of ABO and Rh blood types was found to be quite different in different samples of patients [18][19][20][21][22][23][24][25]. According to those findings, we assume that certain connection between predisposition to CDH and frequencies of ABO and Rh blood types exists.…”
Section: Introductionmentioning
confidence: 54%
“…Nanao Island, a relatively isolated island of about 105 km 2 with 70,000 residents, locates in the South China Sea of the Chaoshan littoral region, close to Shantou city. According to history, chorography, and genealogy record, it is generally believed that the ancestors of Nanao residents migrated from central plains of China hundreds even thousand years ago, where the above mentioned high-risk regions for EC locate [6][7][8]. In order to provide an up-to-date perspective on the occurrence of cancer in this particular group of people, we embarked on a study to provide an overview of the cancer frequency and incidence rates from 1995 to 2004.…”
Section: Introductionmentioning
confidence: 99%
“…The Sezik's study showed that 48% of the patients with HELLP syndrome had a negative blood type O and RH and they were at a greater risk for the syndrome (29). Min Su et al showed that blood group B has a correlation with heart disease in males and cancer in the upper third of the esophagus (30). The study by Engin et al showed that blood group A was more common in patients with pancreatic cancer and the blood group seems to be a protective agent against pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%